Distinction between Externally vs. Internally Guided Decision-Making: Operational Differences, Meta-Analytical Comparisons and Their Theoretical Implications - Nakao, Takashi; Ohira, Hideki; Northoff, Georg (Frontiers in Neuroscience, 2012)
Most experimental studies of decision-making have specifically examined situations in which a single less-predictable correct answer exists (externally guided decision-making under uncertainty). Along with such externally guided decision-making, there are instances of decision making in which no correct answer based on external circumstances is available for the subject (internally guided decision-making). Such decisions are usually made in the context of moral decision making as well as in preference judgment, where the answer depends on the subject’s own, i.e. internal, preferences rather than on external, i.e. circumstantial, criteria. The neuronal and psychological mechanisms that allow guidance of decisions based on more internally oriented criteria in the absence of external ones remain unclear. This study was undertaken to compare decision making of these two kinds empirically and theoretically. First, we reviewed studies of decision making to clarify experimental–operational differences between externally guided and internally guided decision-making. Second, using MKDA, a whole-brain-based quantitative meta-analysis of neuroimaging studies was performed. Our meta-analysis revealed that the neural network used predominantly for internally guided decision-making differs from that for externally guided decision-making under uncertainty. This result suggests that studying only externally guided decision-making under uncertainty is insufficient to account for decision-making processes in the brain. Finally, based on the review and results of the meta-analysis, we discuss the differences and relations between decision making of these two types in terms of their operational, neuronal, and theoretical characteristics.